2017
DOI: 10.1097/scs.0000000000003650
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Surgical Site Infections After Cranioplasty With Perioperative Bundle

Abstract: A perioperative bundle and monitoring system may help to reduce SSI rates after cranioplasty. This work also indicates how an active surveillance program can successfully change clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 23 publications
0
14
0
1
Order By: Relevance
“…23 Similarly, Liu et al improved postcranioplasty infection rates from 10.5% to 1.8% using an IPB as well as active SSI monitoring. 26 Both studies had remarkably high preintervention SSI rates and a low number of included patients (57 and 199, respectively), as compared to the 520 patients included in our study. Conversely, an IPB addressing perioperative glucose and body temperature control had no effect on SSI.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…23 Similarly, Liu et al improved postcranioplasty infection rates from 10.5% to 1.8% using an IPB as well as active SSI monitoring. 26 Both studies had remarkably high preintervention SSI rates and a low number of included patients (57 and 199, respectively), as compared to the 520 patients included in our study. Conversely, an IPB addressing perioperative glucose and body temperature control had no effect on SSI.…”
Section: Discussionmentioning
confidence: 59%
“…IPBs have reduced SSI rates for a broad range of interventions 34 including colon, 40,45 cardiac, and orthopedic surgery, 27 but also cranial neurosurgery. 17,23,26 In all of the above-mentioned guidelines, standardized surveillance with immediate personal feedback to surgeons is considered key, as this measure by itself reduces SSI. 12 In cranial neurosurgery, male sex, age greater than 60 years, smoking, longer preoperative stay, an operative duration longer than 3 hours, emergency or repetitive surgery, contaminated surgery, the use of implants, and CSF leakage or CSF drainage have been identified as independent risk factors for SSI.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Operative duration is commonly cited in the literature as the most predictive risk factor for a SSI. 6,[13][14][15] Our model also showed that a longer operation significantly increased the risk of reoperation for subsequent SSIs. Any operation over 90 minutes more than doubled the risk.…”
Section: Operative Durationmentioning
confidence: 57%
“…Therefore, at our institution, located in New York City, the United States COVID-19 epicenter, we have applied the momentum gained introducing new infection control practices and procedures to prevent of COVID-19 transmission to the adoption of a surgical infection control bundle (Table 1). Implementation of a SSI control bundle has been previously shown to potentially reduce neurosurgery and spine SSI [16][17][18][19][20][21][22][23][24]. However, this effort requires a multi-disciplinary approach involving OR nurses and staff, anesthesia, infection control, and neurosurgeons.…”
Section: To the Editormentioning
confidence: 99%